Glutathione and selenium nanoparticles have a synergistic protective effect during cryopreservation of bull semen - Li, Shubin; Ren, Jingyu; Zhang, Wenqi; Wang, Biao; Ma, Yuzhen; Su, Liya; Dai, Yanfeng; Liu, Gang (Frontiers in Veterinary Science, 2023)
In the present study, the synergistic protective effect of co-supplementation of glutathione (GSH) with selenium nanoparticles (SeNPs) on the cryopreservation efficiency of bull semen was analyzed. After collection, the ejaculates of Holstein bulls were subsequently diluted with a Tris extender buffer supplemented with different concentrations of SeNPs (0, 1, 2, and 4μg/mL), followed by semen equilibration at 4℃ and assessment of sperm viability and motility. Subsequently, the ejaculates of Holstein bulls were pooled, split into 4 equal groups, and diluted with a Tris extender buffer supplemented with basic extender (negative control group, NC group), 2μg/mL SeNPs (SeNPs group), 4mM GSH (GSH group), and 4mM GSH plus 2μg/mL SeNPs (GSH+SeNPs group). After cryopreservation, motility, viability, mitochondrial activity, plasma membrane integrity, acrosome integrity, concentration of malondialdehyde (MDA), superoxide dismutase (SOD), and catalase (CAT), and ability of frozen-thawed sperm cells to support in vitro embryonic development were evaluated. The results showed that no side effect of SeNPs concentrations applied in the current study on the motility and viability of equilibrated bull spermatozoa was found. Meanwhile, supplementation of SeNPs significantly promoted the motility and viability of equilibrated bull spermatozoa. Furthermore, the co-supplementation of GSH with SeNPs effectively protected bull spermatozoa from cryoinjury as expressed by promoting semen motility, viability, mitochondrial activity, plasma membrane integrity, and acrosome integrity. Finally, the enhanced antioxidant capacity and embryonic development potential in the frozen-thawed bull spermatozoa cryopreserved by co-supplementation of GSH with SeNPs further confirmed the synergistic protective effect of co-supplementation of GSH with SeNPs on the cryopreservation of bull semen.